Re-thinking the role of the dorsal striatum in egocentric/response strategy - BOTREAU, Fanny; Gisquet-Verrier, Pascale (Frontiers in Behavioral Neuroscience, 2010)
Rats trained in a dual-solution cross-maze task, which can be solved by place and response strategies, predominantly used a response strategy after extensive training. This paper examines the involvement of the medial and lateral dorsal striatum (mDS and lDS) in the choice of these strategies after partial and extensive training. Our results show that rats with lDS and mDS lesions used mainly a response strategy from the early phase of training. We replicated these unexpected data in rats with lDS lesions and confirmed their tendency to use the response strategy in a modified cross-maze task. When trained in a dual-solution water maze task, however, control and lesioned rats consistently used a place strategy, demonstrating that lDS and mDS lesioned rats can use a place strategy and that the shift towards a response strategy did not systematically result from extensive training. The present data did not show any clear dissociation between the mDS and lDS in dual solution tasks. They further indicate that the dorsal striatum seems to determine the strategies adopted in a particular context but cannot be considered as a neural support for the response memory system. Accordingly, the role of the lateral and medial part of the dorsal striatum in egocentric/response memory should be reconsidered.